2019
DOI: 10.1021/acsmedchemlett.9b00118
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective and Efficient Synthesis of 7-Aminoquinolines and Their Applications as Golgi-Localized Probes

Abstract: Quinoline derivatives have extensively been used for both pharmaceutical agents and bioimaging. However, typical synthesis of quinoline derivatives is generally through strong acid/base-catalyzed or metal-catalyzed methods at high temperatures. Here we report a catalyst-free synthesis of 2,4-disubstituted 7-aminoquinolines with high selectivity and good yields via the introduction of a trifluoromethyl group. It is discovered that quinolines containing both amino and trifluoromethyl groups exhibit strong intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Because of the strong electronegativity of the fluorine atom and the large bond energy of the C–F bond, not only the stability of the corresponding compound is enhanced, but also its fat solubility is improved. So it can easily enter the Golgi apparatus through the barrier of the membrane because of its lipophilicity. , Therefore, we reasonably speculate the 4-CF 3 -substituted quinoline derivatives can specifically target the Golgi apparatus . Mounting studies have demonstrated that the azido group is an excellent recognition receptor because of its easy introduction and high specificity to H 2 S. So an azide-based fluorescent probe, Gol-H 2 S , was reasonably constructed by employing 4-CF 3 -substituted 7-aminoquinoline (compound 1 ) with a strong push–pull structure as a fluorophore.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the strong electronegativity of the fluorine atom and the large bond energy of the C–F bond, not only the stability of the corresponding compound is enhanced, but also its fat solubility is improved. So it can easily enter the Golgi apparatus through the barrier of the membrane because of its lipophilicity. , Therefore, we reasonably speculate the 4-CF 3 -substituted quinoline derivatives can specifically target the Golgi apparatus . Mounting studies have demonstrated that the azido group is an excellent recognition receptor because of its easy introduction and high specificity to H 2 S. So an azide-based fluorescent probe, Gol-H 2 S , was reasonably constructed by employing 4-CF 3 -substituted 7-aminoquinoline (compound 1 ) with a strong push–pull structure as a fluorophore.…”
Section: Methodsmentioning
confidence: 99%
“…39,40 Therefore, we reasonably speculate the 4-CF 3substituted quinoline derivatives can specifically target the Golgi apparatus. 22 Mounting studies have demonstrated that the azido group is an excellent recognition receptor because of its easy introduction and high specificity to H 2 S. 25−28 So an azide-based fluorescent probe, Gol-H 2 S, was reasonably constructed by employing 4-CF 3 -substituted 7-aminoquinoline (compound 1) with a strong push−pull structure as a fluorophore. In the synthesis of probe Gol-H 2 S, the amino group was easily modified to the azido moiety.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for fluorophores, we chose aminoquinoline derivatives because of their outstanding Golgi-targeting capability and desirable photophysical properties. 63,64 Therefore, we synthesized the probe GT-GSH based on 4-CF 3 -7aminoquinoline for highly sensitive and selective detection of GSH (Scheme 1). The free probe GT-GSH emits blue fluorescence because the amino group is protected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Herein, employing Förster resonance energy transfer (FRET) and intramolecular charge transfer (ICT) principles, we designed a Golgi-targeting and dual-color “Turn-On” probe Q-RVRR-DCM for spatially precise imaging of intracellular furin, as schematically illustrated in Figure a. In our design, the quinoline dye (Q) was selected as a Golgi-targeting fluorophore, which could specifically localize in the Golgi apparatus. Dicyanomethylene-4 H -pyran (DCM) was chosen as another fluorophore because it provides not only a large Stokes shift but also a superb fluorescent yield owing to its ultrafast ICT process. Q and DCM were connected by the Arg-Val-Arg-Arg (RVRR) peptide linker, acting as the energy donor and acceptor in the FRET system, respectively. In Q-RVRR-DCM , Q almost does not emit fluorescence due to the FRET process from Q to DCM.…”
Section: Introductionmentioning
confidence: 99%